After 2000 Stože landslide - Mikoš, Matjaž (Acta hydrotechnica, 2021)
More than 20 years after the 2000 Stože Landslide that devastated the village of Log pod Mangartom in NW Slovenia, this paper gives a review of the short-term response to and disaster relief provided for this catastrophic event, and further summarises this events effects on Slovenias efforts to improve its system of preventing natural disasters caused by various forms of landslides. Recent advances in reducing landslide disasters in Slovenia after 2000 are presented, including hazard and risk maps for landslides, rockfalls, and debris flows based on modern methodologies. Also, a short overview is given of Slovenian international cooperation on natural disasters. The developments in the landslide disaster risk reduction policy have unfortunately been less obvious in terms of the state taking preventive measures by adopting relevant legislation for adequate spatial planning.
Keywords: debris flows; drobirski tok; hazards; landslides; legislation; naravne nesreče; natural disasters; nevarnosti; risks; Slovenia; Slovenija; Stože landslide; tveganja; zakonodaja; zemeljski plaz Stože; zemeljski plazovi